Hubungan Asupan Zat Gizi Makro, Pengetahuan Gizi, dan Aktivitas Fisik dengan IMT Mahasiswa FKM UNDANA - Boby Yitran Udju Tade; Marselinus Laga Nur; Anna Henny Talahatu (Yayasan Literasi Sains Indonesia, 2025)
Currently, Indonesia is facing three burdens of nutrition problems (triple burden). This nutritional problem also occurs in students. This is because it is influenced by macronutrient intake, nutritional knowledge and also physical activity which are factors related to the body mass index (BMI) of students, BMI is a simple way used to monitor and determine nutritional status. This study aims to analyze the relationship between macronutrient intake, nutritional knowledge and physical activity with the BMI of FKM UNDANA students. This type of research is observational analysis using a cross-sectional design. The sampling technique used simple random sampling with a total of 113 respondents. The statistical analysis used is chi-square using SPSS software. From the results of the analysis, significant values were obtained in carbohydrate intake (p=0.001), protein intake (p=0.702), fat intake (p=0.002), nutritional knowledge (p=0.002) and physical activity (p=0.852). Therefore, it can be concluded that carbohydrate intake, fat intake and nutritional knowledge have a significant relationship with student BMI, while protein intake and physical activity do not have a significant relationship with student BMI.